Economic evaluation of statins in high-risk patients treated for primary and secondary prevention of cardiovascular disease in Greece - Fragoulakis V; Kourlaba G; Maniadakis N (Dove Medical Press, 2012)
Vassilis Fragoulakis, Georgia Kourlaba, Nikolaos ManiadakisDepartment of Health Services and Management, National School of Public Health, Athens, GreeceBackground: An economic evaluation was undertaken in order to assess several therapeutic alternatives (rosuvastatin, atorvastatin, simvastatin, and pravastatin) for the prevention of primary and secondary cardiovascular events in high-risk patients in Greece.Methods: A probabilistic Markov model with five distinct states provided estimates over a 20-year time span. The relative effectiveness of comparators was based on the literature. The HellenicSCORE risk equation was used to forecast survival. The transition probabilities from acute myocardial infarction or stroke to death were estimated with reference to the Framingham study. In addition, Framingham scores were used to calculate the probability of nonfatal acute myocardial infarction or nonfatal stroke. Costs were estimated from the perspective of sickness funds and included direct medical costs valued in the year 2012. The total treatment cost accounted for the cost of drugs, routine examinations, and resources expended in the management of acute myocardial infarction, stroke, and death. The utility decrements used are those for the Greek population. A supplementary budget impact analysis was also conducted.Results: The mean discounted quality-adjusted life years in the case of males for the rosuvastatin arm were 10.18 versus 10.04, 9.94, and 9.88 for atorvastatin, simvastatin, and pravastatin, respectively. The mean total cost was €15,392, €16,438, €17,009, and €17,356 for rosuvastatin, atorvastatin, simvastatin, and pravastatin, respectively. Similar results were obtained in the case of females, while all analyses demonstrated a statistically significant difference at the 95% level of significance. The total burden of 100% (single) use of rosuvastatin in a hypothetical cohort of 100 male patients for one year was €1.47 million versus €1.53 million for atorvastatin, €1.57 million for simvastatin, and €1.59 million for pravastatin.Conclusion: Rosuvastatin may represent an attractive choice compared with likely alternative existing therapies used in the primary and secondary prevention of cardiovascular events by the National Health Service of Greece.Keywords: cost utility, statins, rosuvastatin, cardiovascular disease